The drosophila fragile X protein dFMR1 is required during early embryogenesis for pole cell formation and rapid nuclear division cycles. - Deshpande, G.; Calhoun, G.; Schedl, P. (Genetics, 2006)
The FMR family of KH domain RNA-binding proteins is conserved from invertebrates to humans. In humans, inactivation of the X-linked FMR gene fragile X is the most common cause of mental retardation and leads to defects in neuronal architecture. While there are three FMR family members in humans, there is only a single gene, dfmr1, in flies. As in humans, inactivation of dfmr1 causes defects in neuronal architecture and in behavior. dfmr1 has other functions in the fly in addition to neurogenesis. Here we have analyzed its role during early embryonic development. We found that dfmr1 embryos display defects in the rapid nuclear division cycles that precede gastrulation in nuclear migration and in pole cell formation. While the aberrations in nuclear division are correlated with a defect in the assembly of centromeric/centric heterochromatin, the defects in pole cell formation are associated with alterations in the actin-myosin cytoskeleton.